Organisational innovations in health resort-based tourism - Szymańsk, Elżbieta; Dziedzic, Ewa; Rutkowski, Andrzej (Business: Theory and Practice, 2017)
The main goal of the paper is to enhance knowledge in the scope of fundamental research, in the fields of economics and management sciences, by creating the theoretical model of organisational innovation process at the health resort-based tourism. In addition to the theoretical model the authors present examples of the most important organizational innovations used in the surveyed objects. The authors used the mapping method, the Delphi method and the standardised interview method. The direct result of the research involves the model of the health resort-based tourism organisational innovativeness. The project, as it has already been written above, has the innovative nature. So far organizational innovations taking place in the health resort-based tourism were not described and no model of the innovativeness process. The expected results will have an effect on the development of economic sciences, especially management sciences. The results will also contribute to social development through the possibility of using the research results by practicians – organizers of health resort-based tourism.